NEWSPAPERS AS ESSENTIAL FACTOR OF NEOLOGISM FORMATION (Academia Science Repository, 2023)
At the moment all the languages are experiencing a “neological boom,” which is associated with radical changes in contemporary world. The theory of neology in world studies has not yet been finalized as an independent area of lexicology. It appeared and began to develop intensively at the end of the twentieth century. At present, we are talking about the development of two system disciplines – the lexicology of neologisms (neology) and the lexicography of neologisms (neography).